Greenhouse gas emissions from the US liquefied natural gas operations and shipping through process model based life cycle assessment - Mainak Mukherjee; James Littlefield; Harshvardhan Khutal; Krista M. Kirchner-Ortiz; Kaitlyn G. Davis; Liang Jing; Farah Ramadan; Hassan El-Houjeiri; Mohammad S. Masnadi; Adam R. Brandt (Communications Earth & Environment)
Abstract Given the increasing importance of liquefied natural gas in the global energy system, an understanding of natural gas value chain Greenhouse gas emissions is increasingly important. Here, we develop models of the key unit processes in the liquefied natural gas value chain: liquefaction, shipping, and regasification. We utilize detailed process-level data for liquefaction terminals and ships to generate granular estimates. Average gate-to-gate emissions of 0.220 and 0.269 tonnes of CO2e/tonne gas liquefied were estimated for US liquefied gas exported from Sabine Pass and Cove Point liquefaction terminals, respectively. Furthermore, 331 voyages are modeled from four US ports reaching 30 countries, and the average gate-to-gate emissions for the countries to Asia are the highest at 0.200 tonnes CO2e/tonnes of gas delivered. The estimated average gate-to-gate emissions for regasification terminals is 0.021 tonnes CO2e/tonne of gas regasified. The developed models can be expanded to other regions, offering a global analysis provision.